2013
DOI: 10.5692/clinicalneurol.53.217
|View full text |Cite
|
Sign up to set email alerts
|

A case of subacute parkinsonism presenting as bilateral basal ganglia legions by MRI in diabetic uremic syndrome

Abstract: A 60-year-old male was admitted because he had developed tremulous movement in both upper and lower limbs and gait disturbance over the course of 3 months. He had been on continuous ambulatory peritoneal dialysis almost 1 year earlier due to end-stage diabetic nephropathy. A neurological examination revealed a mild disturbance of his consciousness, asterixis in the upper limbs, bilateral extensor plantar responses and parkinsonism, which were characterized by bradykinesia, akinesia, rigidity, and bilaterally t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…To our knowledge, this is the largest cohort which followed patients with uremia without or with BG lesions and its related movement disorders for 2 years to determine their clinical and neuroimaging outcomes. In the literature, there are approximately 40 case reports of extrapyramidal movement disorders due to BG lesions with uremia [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] . Among them, only Wang and Cheng 5 prospectively studied six patients with uremia who had BG-related movement disorders.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the largest cohort which followed patients with uremia without or with BG lesions and its related movement disorders for 2 years to determine their clinical and neuroimaging outcomes. In the literature, there are approximately 40 case reports of extrapyramidal movement disorders due to BG lesions with uremia [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] . Among them, only Wang and Cheng 5 prospectively studied six patients with uremia who had BG-related movement disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Other symptoms of the syndrome include disturbances in consciousness, dysarthria, dysphagia, and chorea. [1][2][3][4] Neurologic symptoms improve in some patients, and lesions usually regress (as assessed by conventional MRI); however, the overall prognosis is poor in the majority of cases. 1 The diffusion abnormalities observed in the present case were consistent with those reported previously.…”
mentioning
confidence: 99%
“…8 In addition, a human study demonstrated that cerebral vasodilatory capacity is decreased in patients with anemia secondary to chronic renal failure, 9 indicating that anemia deserves more attention, although hematologic findings have rarely been described in this syndrome. 3 Considering the frequent occurrence of peridialytic blood pressure changes, 10 it is tempting to speculate that blood pressure changes contribute to failed autoregulation of perforating arteries, resulting in edematous lentiform nucleus lesions in cases of long-term kidney failure, particularly in those with diabetes and anemia. The present case highlights the clinical and radiologic characteristics of diabetic uremic syndrome, or, more precisely, uremic lenticulostriate syndrome.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The most prominent MRI findings were T1‐hyperintense lesions involving the basal ganglia in C‐NKH patients and T2‐hyperintense lesions involving the basal ganglia in C‐URE patients. These distinctive MRI features provide indications of the different pathogenic mechanisms that occur in the basal ganglia, although the precise mechanisms remain unclear …”
Section: Discussionmentioning
confidence: 99%